The genus Nepeta: Traditional uses, phytochemicals and pharmacological properties. (25th March 2021) - Sharma, Ajay; Cooper, Raymond; Bhardwaj, Garima; Cannoo, Damanjit Singh
Abstract: Ethnopharmacological relevance: Nepeta is a multiregional genus of the "Lamiaceae" (Labiatae or Mint) family. Species of Nepeta are a valuable part of traditional medicine and used extensively, particularly in the Himalayan region of India (Uttarakhand, Himachal Pradesh, Jammu and Kashmir, Leh-Ladakh), Pakistan (Khyber Pakhtunkhwaand Pakistani Kashmir), Nepal (Baglund district), also in China and hilly regions of Turkey and Iran. Nepeta s pecies are extensively used as a remedy against a variety of ailments and conditions like chicken pox, tuberculosis, malaria, pneumonia, influenza, measles, stomach disorders, eye complaints, respiratory disorders, asthma, colds, coughs etc. Aim of the review: The main aim of this review is to present a comprehensive and detailed study on traditional uses, pharmacology, phytochemistry, toxicology of Nepeta species and suggest future direction on the design and conduct of various preparations, either alone or in blends with prevailing conventional remedies. The review also emphasizes encouraging researchers towards the wide range of pharmaceutical applications of the various species of Nepeta for their better use and exploration in the future. Material and methods: All the relevant data and information on different species of Nepeta were assembled using different databases, such as Science Direct, Springer, PubMed, Taylor and Francis imprints, Chemspider, Google scholar, review and research articles from peer-reviewed journals and unpublished data. Some select 'grey literature' sources viz. ethnobotanical books, chapters, Wikipedia and webpages were also studied. Results: A variety of bioactive secondary metabolites and nutraceuticals has been isolated from various species of Nepeta . These bioactive compounds belong to different classes of secondary metabolites, such as phenolic acids and their glycosides (rosmarinic acid, gallic acid, caffeic acid), flavonoids and their glycosides (cirsimaritin, salvigenin, luteolin, apigenin), iridoids (nepetalactones and their derivatives), terpenoids (1, 8-cineole, linalool, β-caryophyllene, germacrene D, parnapimaro, β-amyrin, oleanolic acid, ursolic acid), steroids (β-sitosterol, stigmasterol), lignans, amino acids, carbohydrates, volatile oils, etc. The species of the genus Nepeta possess a variety of pharmacological activities namely anti-inflammatory, anti-nociceptive, anti-alzheimer, anticancer and cytotoxic, antioxidant, immunomodulatory, antimicrobial, antifungal, insecticidal and along with other biological activities. Conclusion: The species of the genus Nepeta contains a rich source of various bioactive compounds, which are well tolerated as traditional medicines. In fact, different species of Nepeta are widely used in a variety of traditional medicinal systems all around the world. Owing to the variety of pharmacological properties of Nepeta species, more comprehensive and inclusive clinical trials are necessary for the utilization of different Nepeta species against the treatment of a wide range of ailments. There are also various other uses such as food, cosmetic and agriculture that can be investigated or explored in future. Some of the major domains that can be explored within this genus are the investigation of different species for their unexplored biological potential, isolation and characterization of new bioactive constituents and finally, investigation of new applications and possible commercialization of these bioactive leads. No doubt, there are various viable research domains outside those discussed above, but presently for the purposes of this review we will only emphasize the activities herein. Graphical abstract: Image 1 Highlights: Nepeta spp. are an excellent source of bioactive secondary metabolites and nutraceuticals. Most of the Nepeta spp. are annual and perineal herbs and aromatic in nature. Only few Nepeta species have been analysed with respect to their bioactive polyphenolic, terpenoids and steroids. Traditionally, Nepeta spp. are used against snake and scorpion bites, many heart problems, liver and kidney diseases. Nepeta spp. are known to possess variety of pharmacological properties viz. anti-inflammatory, analgesic, anticancer, antioxidant, antimicrobial etc.